Rem(a)inders: Mormon Pioneers’ Life Writings - Coelho, Adriane Rodrigues (Em Tese, 2007)
Understanding that literature, history and memory interweave,this essay aims at showing the importance of nineteenthcenturyMormon personal literature as both historicaldocuments and literary texts, and, at the same time,emphasizing its importance for conveying and maintainingvalues and collective memories, which ultimately provide thegroup with a sense of identity.